External ophthalmomyiasis by Oestrus ovis treated with tobacco: clinical case report and medical literature review - García Guerrero, Carlos Jair; Garza Quiñones, Jesús; Reza Caballero, Jorge; González Treviño, Juan Luis (UANL. Facultad de Medicina, 2014)
External ophthalmomyiasis is an infestation of conjunctiva with larvae or maggots of certain lies. Oestrus ovis is the most common cause of human ophthalmomyiasis. The case of a 16-yearold female is described, who presented with foreign body sensation, pain, and redness in the left eye. Slit-lamp biomicroscopy revealed 32 tiny larvae crawling around the conjunctival sac. The larvae were mechanically removed under topical anesthesia, and identiied under a light microscope as irst-stage larvae of O. ovis causing external ophthalmomyiasis. She was successfully treated with topical tobacco juice. Follow-up examination of these cases is recommended to avoid possible complications.